CGIAR 2030 global strategy for resilient drylands - International Center for Agricultural Research in the Dry Areas; International Crops Research Institute for the Semi-Arid Tropics (International Center for Agricultural Research in the Dry Areas, 2024)
The CGIAR 2030 Global Strategy for Resilient Drylands has been developed to align with the 2030 CGIAR Research and Innovation Strategy. It presents the informed and coordinated approach that CGIAR will take to contribute to the sustainable and resilient transformation of dryland agrifood systems, building on our unique value proposition and track record of co-creating and co-delivering innovative research and impact in the drylands.